Pengaruh Kompensasi, Lingkungan Kerja dan Beban Kerja Terhadap Retensi Karyawan (Studi Kasus Pada Karyawan PT. Inter Nusa Kreasindo Energy) - Tsabbat Araaf; Anita Novialumi (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Employee retention has become an important issue in the renewable energy industry due to the increasing demand for skilled human resources and operational challenges faced by companies. A high employee turnover rate can affect productivity and the sustainability of company operations. This study aims to analyze the influence of compensation, work environment, and workload on employee retention at PT Inter Nusa Kreasindo Energy. This study employed a quantitative approach using primary data collected through questionnaires distributed to 61 employees using a saturated sampling technique. Data analysis was conducted using SmartPLS version 4 to examine the relationships among the research variables. The results showed that compensation had a positive and significant effect on employee retention, with a coefficient value of 0.351, a T-statistic value of 3.916, and a p-value of 0.000. Workload also had a positive and significant effect on employee retention, with a coefficient value of 0.363, a T-statistic value of 2.548, and a p-value of 0.011. Meanwhile, the work environment had a positive but insignificant effect on employee retention, with a coefficient value of 0.239, a T-statistic value of 1.659, and a p-value of 0.097. This study indicates that compensation and effective workload management can improve employee retention, while the work environment has not shown a significant influence on employees’ decisions to remain in the company. Therefore, companies are expected to improve compensation systems and workload management effectively in order to maintain employee retention and support organizational sustainability.